2015
DOI: 10.1016/j.brs.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Val66Met BDNF Gene Polymorphism Influences Human Motor Cortex Plasticity in Acute Stroke

Abstract: Background-BDNF gene polymorphism impacts human motor cortex function and plasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 34 publications
(47 reference statements)
2
59
0
1
Order By: Relevance
“…While interest has centred on genes known to contribute to neuroplasticity (27), there are a number of candidate biomarkers to consider as well as gene-gene interactions, and epigenetics.…”
Section: Theme 2: Recovery Biomarkersmentioning
confidence: 99%
“…While interest has centred on genes known to contribute to neuroplasticity (27), there are a number of candidate biomarkers to consider as well as gene-gene interactions, and epigenetics.…”
Section: Theme 2: Recovery Biomarkersmentioning
confidence: 99%
“…23 Individuals' genetic profiles may also influence recovery. [24][25][26] While interest has centred on genes known to contribute to neuroplasticity, 27 there are a number of candidate biomarkers to consider as well as gene-gene interactions and epigenetics.…”
Section: Theme 2: Recovery Biomarkersmentioning
confidence: 99%
“…Cortical plastic changes after acute stroke may also be influenced by genetic factors. One study showed that repetitive transcranial magnetic stimulation inducing long term potentiation-like activity differed less between the affected and unaffected hemisphere in patients with the BDNF rs6265, Val66Met polymorphism than those without, and the authors proposed that this may be beneficial in less severe strokes but unfavorable in severe strokes, 30 suggesting that genetic variations may play alternative roles in different settings.…”
Section: Animal Models and Surrogate Markers For Studying Stroke Recomentioning
confidence: 99%
“…10 The BDNF single nucleotide variation (rs6265, Val66Met; Table 1) influences excitability and outcome. 30,31,33 High-frequency repetitive transcranial magnetic stimulation over the primary motor cortex of the affected hemisphere induces positive effects on motor function, and subjects with the Val/Val genotype have better improvement. 29 Long-term mortality after stroke and stroke recurrence genetics has been studied in several studies (Table 1).…”
Section: Neurological/physical Deficitmentioning
confidence: 99%